PEMBENTUKAN KARAKTER CINTA TANAH AIR MELALUI PENDIDIKAN KEWARGANEGARAAN PADA ANAK INDONESIA - Parmin, Umi Na'imah Apriani; Sukartono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
The issue raised by this research relates to the affection that Indonesian immigrant children who attend school in Malaysia have for their own country. The younger generation in Indonesia has to love their country in order for them to grow up to be future national leaders and capable of defending it. Through the identification of factors that support and surmount current challenges, this research seeks to cultivate in Indonesia's youth a love for their country and hometown despite their exile. This study employs a phenomenologically grounded qualitative technique. The head of the learning studio, the class instructor, and three first-grade primary school pupils from the Indonesian Civic Education Center (PPWNI) in Klang, Malaysia, served as study informants. Techniques for gathering data include observation, documentation, and interviews. This study employs source triangulation and technology to guarantee data accuracy. The data analysis for this study involved four stages: gathering data, analyzing data, presenting data, and drawing conclusions. Interactive analytical models are utilized for this. According to research findings, Civic Education sessions that highlight these characteristics help pupils at the Indonesian Civic Education Center (PPWNI) in Klang, Malaysia, demonstrate a sense of love for their nation. Using home products, appreciating Indonesia's natural beauty and culture, learning the national song by heart, and enjoying domestic travel are a few of them. The purpose of this study is to enhance the character education and patriotism that Indonesian youngsters get at Learning Studio Malaysia, which has not yet been executed to the best of its abilities.